Reform Strategies for the Popular Music Public Course Based on Key Competences - Huang, Xiaoxia; Phokha, Pramote; Chiangthong, Nut (Journal of Ecohumanism, 2024)
This study aims to explore the application potential of international music teaching methods in the reform of public basic courses of popular music in Chinese universities. Using mixed research methods, the applicability of Dalcroze, Kodaly, and Orff teaching methods was systematically evaluated through expert interviews, teaching material development, and a quasi-experimental design. The study found that these methods have high overall applicability in the Chinese higher education environment (average rating 4.183/5), but require localization adjustments. Based on this, the innovative textbook "Fundamentals and Applications of Popular Music" (IOC value 0.920) and a 12-week teaching plan (IOC value 0.880) were developed. The results of the 16-week teaching experiment showed that the students in the experimental group were significantly better than the control group in terms of music theory knowledge, appreciation ability, creative ability and learning interest (p<0.01). This study proposes a curriculum reform strategy that integrates innovation, technology empowerment, and interdisciplinary integration, providing theoretical basis and practical guidance for improving the quality of popular music education in colleges and universities. Future research directions include expanding the sample scope, conducting long-term follow-up studies, and deepening cross-cultural comparative analysis.